Beg to Differ - Agassi, Joseph. author. aut Link
X, 138 p. 1 illus.
Keywords: This book is an attempt to familiarize readers in a very simple and easy manner the rules and proper procedures of rational debate. It will help reduce the frustration that many experience when engaging in debates. The proper conduct of debate is both fun and mentally stimulating, and we trust that implementing the rules of debate outlined in this book will help you and your friends increase your ability to learn, improve and engage in rational and intellectual debates.